The cutting edge: a survey of technological innovation. - Greek, Cecil E. (Federal Probation, 2000)
The writer presents a survey of new developments in technology that will either enhance or complicate the lives of those in corrections and criminal justice. He contends that the role of technological innovation is one of the most important issues facing criminal justice at the beginning of the 21st century. He asserts that controversies in relation to privacy, government tracking of citizen behaviors, and access to public records will increase as technology improves in these areas and more information can become available online.